Eco-Hotel At The Balige Natural Resort Area - Siregar, Hizkia Sahatasi; Siahaan, Nelson (Jurnal Koridor, 2019)
With a tourism development discourse in Lake Toba, North Sumatra, the tourism minister is targeting up to 1 million tourists to visit Lake Toba in 2019. Therefore, it is necessary to develop a stay and relaxation that can support tourist activities in Lake Toba. At the moment there is no housing to stay and relax at the same time at Balige. Therefore, it is necessary to design a house to rest and relax in there. The Resort hotels in the Balige Nature Tourism Area are expected to be a destination for local and foreign tourists. The Resort Hotels in the Balige Nature Tourism Area are using the concept of "Ecological Architecture,â€™ where with the presence of this resort hotel the balance of nature and relationships between human, environment, and building are maintained in balance. The design of â€œResort Hotel in The Balige Nature Tourism Areaâ€ is needed research to get an optimal design. Then, on the design of the project used a qualitative methodology. Resort Hotel Design in the Balige Nature Tourism Area can fulfill human needs for vacationing, relax and resting from all the daily activities in the city. The design of resort hotels can also support government programs that promote tourism in the area of Lake Toba.